Effect of Flow Rate on the Corrosion Behavior of P110 Steel in High-Ca2+ and High-Cl− Environment - Ya-Ni Zhang; Shao-Gang Zhang; Jin-Heng Luo; Yan Long; Nan Ji; Bing Fan; Si-Min Wang (Metals, 2022)
With the exploitation of oil and gas resources, the water environment of high-Ca2+ and high-Cl− stratum puts forward high safety requirements for tubular columns. This paper simulates the underground environment by using high-temperature and high-pressure autoclaves, combines electrochemical research results, and analyzes the effect of flow rate on the corrosion behavior of P110 steel in a water environment of 7.5 g/L Ca2+ + 128 g/L Cl− simulated stratum. The research results show that the presence of Ca2+ promotes the acidification of the solution and accelerates the dissolution of P110 steel. With the increased flow rate of the fluid, the corrosion rate of P110 steel increases, but the increasing trend slows down gradually. At the same time, the flow rate decreases the probability of corrosive pitting on P110 steel. The decreasing is closely related the peeling of earlier CaCO3 precipitation by the fluid.